2022
DOI: 10.1101/2022.06.09.495447
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene structure heterogeneity drives transcription noise within human chromosomes

Abstract: Classical observations have long suggested there is a link between 3D gene structure and transcription. However, due to the many factors regulating gene expression, and to the challenge of visualizing DNA and chromatin dynamics at the same time in living cells, this hypothesis has been difficult to quantitatively test experimentally. Here we take an orthogonal approach and use computer simulations, based on the known biophysical principles of genome organisation, to simultaneously predict 3D structure and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 61 publications
(95 reference statements)
3
9
0
Order By: Relevance
“…This computer model combines several mechanisms of chromosome organization and genomic information. Stochastic simulations from open conformations showed that chromatin forms distinct topologies rather than folding into a single structure [34]. This result is consistent with our findings and the conclusion this paper.…”
Section: Coexisting Topologiessupporting
confidence: 93%
“…This computer model combines several mechanisms of chromosome organization and genomic information. Stochastic simulations from open conformations showed that chromatin forms distinct topologies rather than folding into a single structure [34]. This result is consistent with our findings and the conclusion this paper.…”
Section: Coexisting Topologiessupporting
confidence: 93%
“…This would manifest as increased cell-cell variation in mRNA levels, which we observed for most of the developmentally important genes we assayed by single molecule RNA FISH. Recent studies have similarly reported that disruptions in chromatin 3D organization increase variability in gene expression, using single-cell RNA-seq 69 , RNA-FISH and flow-cytometry 70 , or integrative modeling of omics data 71 . Whether and how these acute changes in cell-cell variability due to disruption of chromatin structure connect to functional outcomes of cohesin loss or reduction in development and disease [72][73][74][75][76][77] will require future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, it is widely believed that TADs remain largely invariant in cells with very different transcriptional programs -which points to little role for transcription in determining structure [5] (for an opposing view, see [6]). On the other hand, clusters of active polymerases -called phaseseparated condensates, hubs, and transcription factories [4,[7][8][9][10] -locally stabilise surrounding clouds of loops, thereby providing an example of a structural unit with a clear functional role.…”
Section: Introductionmentioning
confidence: 99%